Plasma amyloid-beta oligomer is related to subjective cognitive decline and brain amyloid status - Keun You Kim; Jaesub Park; Yong Hyu Jeong; Hyun Jeong Kim; Eun Lee; Jin Young Park; Eosu Kim; Woo Jung Kim (Alzheimer’s Research & Therapy, 2022)
Abstract Background Subjective cognitive decline (SCD) is a target for Alzheimer’s disease prediction. Plasma amyloid-beta oligomer (AβO), the pathogenic form of Aβ in blood, has recently been proposed as a novel blood-based biomarker of AD prediction by representing brain Aβ deposition. The relationship between plasma AβO, brain Aβ deposition, and SCD in individuals with normal objective cognition has not been investigated. Methods In this cross-sectional study, we analyzed 126 participants with normal objective cognition. More SCD symptoms were expressed as higher scores of the Subjective Cognitive Decline Questionnaire (SCDQ) and Memory Age-associated Complaint Questionnaire (MACQ). The plasma AβO level of each participant was measured twice for validation and expressed as a concentration (ng/mL) and a ratio relative to the mean value of two internal standards. Brain Aβ deposition was assessed by [18F] flutemetamol positron emission tomography (PET) and expressed as standard uptake value ratio (SUVR). Associations of SCDQ and MACQ with plasma AβO levels or SUVR were analyzed in multiple linear regression models. The association between plasma AβO level and flutemetamol PET positivity was assessed in logistic regression and receiver operative characteristic analyses. Results Overall, participants were 73.3 years old with female predominance (69.0%). After adjustment for confounders, high SCDQ and MACQ scores were associated with the high plasma AβO levels as both concentrations and ratios (ratios: standardized coefficient = 0.246 and p = 0.023 for SCDQ, standardized coefficient = 0.209 and p = 0.029 for MACQ; concentrations: standardized coefficient = 0.257 and p = 0.015 for SCDQ, standardized coefficient = 0.217 and p = 0.021 for MACQ). In contrast, SCDQ and MACQ were not significantly associated with SUVRs (p = 0.134 for SCDQ, p = 0.079 for MACQ). High plasma AβO levels were associated with flutemetamol PET (+) with an area under the curve of 0.694 (ratio) or 0.662 (concentration). Combined with APOE e4, plasma AβO presented area under the curves of 0.789 (ratio) and 0.783 (concentration). Conclusions Our findings indicate that the high plasma AβO level could serve as a potential surrogate biomarker of severe SCD and the presence of brain Aβ deposition in individuals with normal objective cognition.